2020
DOI: 10.1002/pat.4955
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus‐containing polyamide Mg(OH)2 nanocomposite coating on surface of poly(vinyl chloride) thin film: Study on thermal stability, flammability, and mechanical properties

Abstract: Surface of poly(vinyl chloride) (PVC) thin films was coated using DOPO‐based polyamide (DBPA) coating and DBPA/Mg(OH)2 nanocomposites (DBPN) coating by dip‐coating process. For this purpose, a new DOPO‐based dicarboxylic acid (DBDA) was synthesized and used for preparation of DBPA and organically surface modification of Mg(OH)2 nanoparticles. The effects of DBPA and DBPN coatings on the morphology, thermal stability, combustion, and mechanical properties of PVC were investigated. The uniform dispersion of Mg(O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…The tensile and flexural properties of the as‐prepared CEMC in this study were noteworthily enhanced compared with those of previously reported CEMC 9 . In the CEMC with low O‐MH content, O‐MH had a toughening effect and could reduce the brittleness of CEMC, 41 which is the key to enhancing the flexural strength and flexural modulus of CEMC. The O‐MH nano‐sheets bore the stress transfer during the stretching process of CEMC, which delayed the fracture of CEMC.…”
Section: Resultsmentioning
confidence: 45%
“…The tensile and flexural properties of the as‐prepared CEMC in this study were noteworthily enhanced compared with those of previously reported CEMC 9 . In the CEMC with low O‐MH content, O‐MH had a toughening effect and could reduce the brittleness of CEMC, 41 which is the key to enhancing the flexural strength and flexural modulus of CEMC. The O‐MH nano‐sheets bore the stress transfer during the stretching process of CEMC, which delayed the fracture of CEMC.…”
Section: Resultsmentioning
confidence: 45%
“…At first MC and MDH were prepared according to previous literature. 9,41 To modify bentonite by melamine cyanurate, in a 100 mL-flask, 1 g bentonite and 15 mL deionized water were added and stirred for 24 h at 25 C. In this period, the resulting slurry was irradiated with ultrasonic waves several times. After that, in a 100-mL beaker, 1 g MC was added to 10 mL of deionized water, and pH was controlled between 4.5 and 5.5 by an HCl solution.…”
Section: Preparation Of Melamine Cyanurate Modified Bentonite (Mb)mentioning
confidence: 99%
“…7 In other words, the preparation of PVC nanocomposites is an extensively valuable method for improving thermal stability, flame retardancy, and preventing the migration of PVC plasticizers. [8][9][10][11][12][13] Inorganic metal hydroxide fillers like aluminum trihydrate (ATH) and magnesium dihydroxide (MDH) have been known as excellent examples of flame retardant materials. [14][15][16] MDH and ATH have exhibited a high effect in reducing the heat released and cooling the combustion zone, delaying the ignition time, and decreasing the weight loss caused by ignition.…”
Section: Introductionmentioning
confidence: 99%
“…First, MDH was synthesized according to the previous procedure. [27] For the surface modification of MDH, PEI as nitrogen-rich polymer was functionalized with the imine groups through the reaction with salicylaldehyde. Briefly, 5 ml of ethanol was poured in 0.5 g of PEI, and was stirred at 60 C for 30 min.…”
Section: Preparation Of Functionalized Pei/ Modified Mdh Nanoparticles (Fpmn)mentioning
confidence: 99%
“…These include the use of flame retardant polymers, [25] incorporation of fire resistance groups into the polymer chain, [26] or the preparation of polymer nanocomposites using modified nanoparticles. [27,28] The resulted polymer nanocomposites show all of the properties of both polymers and nanoparticles, such as ductility, flexibility, thermal, and fire stability. [29][30][31][32][33] One of the most helpful reinforcement is the mineral nanoparticles such as metal oxides and metal hydroxide.…”
Section: Introductionmentioning
confidence: 99%